Y+1=(3x-4)

Simple and best practice solution for Y+1=(3x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y+1=(3x-4) equation:



+1=(3Y-4)
We move all terms to the left:
+1-((3Y-4))=0
We calculate terms in parentheses: -((3Y-4)), so:
(3Y-4)
We get rid of parentheses
3Y-4
Back to the equation:
-(3Y-4)
We get rid of parentheses
-3Y+4+1=0
We add all the numbers together, and all the variables
-3Y+5=0
We move all terms containing Y to the left, all other terms to the right
-3Y=-5
Y=-5/-3
Y=1+2/3

See similar equations:

| m+1013=2 | | 6x–2+3x=–2x+6–5x | | 25=(-8)+9(x+3) | | -x-16=2x-11x | | 5d+10-4=13.5 | | v+12=3 | | |3x+5|=8 | | 5n–12=–3n+4 | | 5/x+4=3/x−2 | | 14=a-3.9 | | n7+5=7 | | 4(6x+3)-20=136 | | 3y/4-2=y/2+4 | | 9x+7=153 | | 4x-1=14x-2 | | -4b-5=3b=9 | | 5(m+7)=80 | | 12/n=17/n-6 | | 37=1-9x | | m5=10 | | x+1/4=2 | | -28=-73x-28+21x | | -29+n=-34 | | -3(4x+4(6x+1)=43 | | -31+s=1 | | x+3—2x+5=10 | | -5=-10+v/2 | | 3/x+6=2/14 | | 6r–3r+3r=12 | | 4x(x+1)+5(x+1)=0 | | 8x—40=—8 | | -15x+2=66 |

Equations solver categories